CONCEPT OF ECOLOGICAL TOURISM AND ITS SOCIAL AND PHILOSOPHICAL SIGNIFICANCE IN THE DEVELOPMENT OF SOCIETY (TAMADDUN NURI JURNALI, 2025)
In the article, the social, philosophical and cultural aspects of ecological tourism, its impact on society and the attitude of people to the natural environment were studied, and scientific research was conducted on the objective necessity and subjective possibilities of studying modern ecotourism, and the motivations for increasing the ecological educational culture of the individual in the ecotourism system.